(untitled) (International Journal of Engineering and Computer Science, 2013)
The need for high performance wireless network connectivity that saves cost, time and mess of wires running across offices and in providing high speed access has continued to attract attention to individuals, private and cooperate organizations in the developing countries. This paper presents a cost effective wireless hotspot model called iWLAN for Electronics Development Institute (ELDI), Awka, Nigeria, that supports multiple user sessions simultaneously. This work present an implementation model of iWLAN as well as conduct an experimental study for an enhanced distributed channel access mechanism of Linksys 300N AP used in this work. The main focus of the study is on SMART intranet traffic engineering and QoS guarantees in the iWLAN model. With the former, we aim at distributing the bandwidth in the iWLAN according to available throughput allocation criterion. With the latter, the objective is to ensure that the performance metrics (throughput and delay) experienced by a user allows for flexible data communication within the high density zones. We present our implemented test bed with Aradial RADIUS server and Cisco Linksys wireless router that support Distributed Coordination Function (DCF) functionality and analyze the test approach for iWLAN model.